Physical and qualitative characters of date palm (Phoenix dactylifera L.) fruits stored under freeze condition (Indian Journal of Arid Horticulture, 2020)
Date palm (Phoenix dactylifera L.) is a nutrient rich fruit crop. Iraq is the center of origin of date palm and it is reported that it is cultivated from more than 6000 years ago. Date palm fruit rich in essential nutrients, vitamins, and minerals which help in enhance the growth and development of human body. It contains 70–80% carbohydrates (fructose and glucose) and minerals like calcium, iron, magnesium, phosphorus, potassium, zinc, selenium and manganese which enhance their nutritional values. Aqueous extracts of date have a potential antioxidant and anti-mutagenic property (Saafi et al., 2009). It is rich source of vitamins, especially ẞ-carotene, thiamine, riboflavin, niacin, ascorbic acid and folic acid (El Hadrami et al., 2011). The major date palm growing areas in India are Kutch (Gujarat), western part of Rajasthan, and certain parts of the Punjab, as well as Tamil Nadu. Area of date palm in Rajasthan is 850 ha with production of 800 tonnes (Singh, 2018). It is well known fact that quality deteriorates at ambient temperature after some days of harvesting. However, frozen storage can be utilized in some fruits and vegetables for long time storage. It enhances the shelf life of produce by decreasing the water activity, inhibits microorganism growth and reduces enzymatic activity (Fellows, 2000). Therefore, present study was planned to evaluate the impact of freeze storage on fruit quality characters of date palm and compare the quality parameter of fresh and stored fruits.
Keywords: potassium; phosphorus; selenium